Financial development and dollarization in Ghana: an empirical investigation - George Tweneboah; John Garchie Gatsi; Michael Effah Asamoah (Cogent Economics & Finance, 2019)
This study strengthens the frontiers of research on the drivers of dollarization in emerging economies by exploring the case of Ghana using the autoregressive distributed lag modelling framework. The data for the study spanned from January 2002 to March 2016. The evidence suggests that dollarization shares a common stochastic trend with exchange rates, inflation, interest rate differential, real output, and financial development. The analysis points to the important roles of exchange rate depreciation and financial development in the evolution of dollarization. Whereas depreciation induces a switch to the use of foreign currency, financial development diminishes the trend. Some policy recommendations to curtail the rising dollarization of the Ghanaian economy have been provided.
Keywords: E41; F21; F40; F41; 330; dollarization; demand for money; autoregressive distributed lag model; cointegration; Ghana